Implant survival of the most common cemented total hip devices from the Nordic Arthroplasty Register Association database - Junnila M; Laaksonen I; Eskelinen A; Pulkkinen P; Havelin LI; Furnes O; Fenstad AM; Pedersen AB; Overgaard S; Kärrholm J; Garellick G; Malchau H; et al. (TAYLOR & FRANCIS LTD, 2025)
Background and purpose According to previous Nordic Arthroplasty Register Association (NARA) data, the 10-year implant survival of cemented total hip arthroplasties (THAs) is 94% in patients aged 65-74 and 96% in patients aged 75 or more. Here we report a brand-level comparison of cemented THA based on the NARA database, which has not been done previously.Patients and methods We determined the rate of implant survival of the 9 most common cemented THAs in the NARA database. We used Kaplan-Meier analysis with 95% CI to study implant survival at 10 and 15 years, and Cox multiple regression to assess survival and hazard ratios (HRs), with revision for any reason as endpoint and with adjustment for age, sex, diagnosis, and femoral head material.Results Spectron EF THA (89.9% (CI: 89.3-90.5)) and Elite THA (89.8% (CI: 89.0-90.6)) had the lowest 10-year survivorship. Lubinus (95.7% survival, CI: 95.5-95.9), MS 30 (96.6%, CI: 95.8-97.4), and C-stem THA (95.8%, CI: 94.8-96.8) had a 10-year survivorship of at least 95%. Lubinus (revision risk (RR)=0.77, CI: 0.73-0.81), Muller (RR =0.83, CI: 0.70-0.99), MS-30 (RR =0.73, CI: 0.63-0.86), C-stem (RR =0.70, CI: 0.55-0.90), and Exeter Duration THA (RR =0.84, CI: 0.77-0.90) had a lower risk of revision than Charnley THA, the reference implant.Interpretation The Spectron EF THA and the Elite THA had a lower implant survival than the Charnley, Exeter, and Lubinus THAs. Implant survival of the Muller, MS 30, CPT, and C-stem THAs was above the acceptable limit for 10-year survival.